Analysis of Work-Related Stress Among Nurses in the Inpatient Ward of RSUD So'e: A Description of Physiological, Psychological, and Behavioral Symptoms - Ninef, Violin Irene; Bhwa, Daeng Agus Vieya Putri; Saefatu, Orgina Amelia (Jurnal Vocational Nursing Sciences (VNUS), 2024)
Introduction: Work stress is a significant issue that can adversely impact both physical and mental health, particularly among healthcare professionals like nurses. It often arises from high patient demands, heavy workloads, and emergency situations requiring quick responses. Objective: This study aims to describe the level of work stress experienced by nurses in the inpatient ward of So'e Regional General Hospital and to identify the associated symptoms. Method: The research employed a descriptive design with a quantitative approach, utilizing a case study format. A structured questionnaire was administered to collect data, involving 115 respondents who work in the inpatient ward. Result: The findings revealed that the majority of nurses experienced work stress categorized as mild, with only a small percentage reporting moderate or severe stress levels. Additionally, the data indicated that the prevalence of physiological, psychological, and behavioral symptoms among the respondents was generally low, suggesting that while stress is present, it may not be at a level that significantly affects their overall health. Conclusion: This study underscores the importance of understanding work stress conditions among nurses. The results provide a foundational overview that can inform the development of targeted stress management interventions in healthcare settings. By addressing these issues, hospitals can improve nurse well-being and enhance the overall quality of healthcare services, ultimately benefiting both staff and patients.